Determinan Profitabilitas pada Industri Makanan dan Minuman Indonesia - Andhatu Achsa; Rian Destiningsih (Universitas Tidar, 2020)
The aim of the paper is analysed equation, liability, sales, and labour on profitability of food and beverage industry in Indonesia from 2016 to 2018. Data analysis techniques used, namely multiple linear regression with panel data. In this paper, panel data is a combination of time series and cross sections on food and beverage industries in Indonesia totaling twenty industries are listed on Indonesia Stock Exchange. The result of Chow and Hausman test, the paper using Fix Effect Model (FEM). This paper concludes that equity and liability variables not significant on profitability of food and beverage industry in Indonesia from 2016 to 2018, sales variable has a negative significant on profitability of food and beverage industry in Indonesia from 2016 to 2018, and labour variable has positive significant on profitability of food and beverage industry in Indonesia from 2016 to 2018.